Amorphous Cu–In–S Nanoparticles as Precursors for CuInSe2 Thin‐Film Solar Cells with a High Efficiency. Issue 7 (16th May 2013) - Ahn, SeJin; Choi, Yoo Jeong; Kim, Kyunhwan; Eo, Young‐Joo; Cho, Ara; Gwak, Jihye; Yun, Jae Ho; Shin, Keeshik; Ahn, Seoung Kyu; Yoon, Kyunghoon
Abstract CuInSe2 (CISe) absorber layers for thin‐film solar cells were fabricated through the selenization of amorphous Cu–In–S nanoparticles, which were prepared by using a low‐temperature colloidal process within one minute without any external heating. Two strategies for obtaining highly dense CISe absorber films were used in this work; the first was the modification of nanoparticle surface through chelate complexation with ethanolamine, and the second strategy utilized the lattice expansion that occurred when S atoms in the precursor particles were replaced with Se during selenization. The synergy of these two strategies allowed formation of highly dense CISe thin films, and devices fabricated using the absorber layer demonstrated efficiencies of up to 7.94 % under AM 1.5G illumination without an anti‐reflection coating.